Regards croisés France-Espagne : réflexions sur les stéréotypes réciproques - Joël Brémond (Amnis)
This paper intends to clarify some generic characteristics of the stereotype. Is it a fossilization of thought, a « ready-to-think » which contributes to an individual and collective mental comfort ? Has it a dialectic role between reinforcement of the human groups and ostracization of the foreigner. Is it universal ? Then, by means of a qualitative study, the mutual stereotypes between French and Spanish people will be taken off. French people often are perceived by the Spanish as hereditary enemies, with a denunciation of their mannerism, their dishonesty, their arrogance and even sometimes their sexual tendencies. Vice versa, the stereotypes developed by the French about Spain and the Spanish people show, first of all, concerning the neighboring country, an extreme ignorance, easily accompanied with a condescending look.